Variações climáticas ao longo do ano e resultados da PIVE em doadoras de diferentes grupos genéticos - Pereira, Anamara (2012)
The objective was to evaluate and compare the effects of genetic group of the donor and climatic variables on results of in vitro embryo production in cattle donors. 2313 results of follicular aspiration were used, which 961 in females of the subspecies Bos taurus taurus and 1352 from donors in the subspecies Bos taurus indicus. The management regime of the animals was the semi-confinement, and the mineral supplementation was ad libitum. The follicular punctures were performed by the same technician, with intervals of at least thirty days. We used ultrasound equipped with intravaginal microconvex sector transducer 5 to 7.5 MHz. All follicles larger than 3 mm were identified and punctured. The cumulus oocyte complexes (COCs) recovered were transferred to plates containing culture medium 60x15mm flush where DPBS were selected, counted and sorted based on their morphological appearance. After their arrival at the laboratory of Biotran Company, the oocytes were transferred to plates where they remain until complete maturation period of 24 hours. The semen used in vitro fertilization (IVF) was thawed at 35°C and evaluated for motility and vigor. IVF was performed after 18 hours in a controlled atmosphere incubator. After seven days of fertilization, the embryos were evaluated in each group. Donors of zebu had higher average recovery of viable and total oocytes and of embryo production in relation to taurus respectively (6.9 vs. 13.2, 11.6 vs. 20.4 and 1.6 vs. 4.0, P <0.05). Whereas genetic groups together will reveal differences in embryo production and total conversion of viable oocytes embryos at different times of the year, only the best conversion trend of embryos in winter (24.37 ± 1.85) compared to summer (20.84 ± 1.57). The average total conversion of oocytes was higher in embryo zebu (23.5 vs. 30.6 - P <0.0001). Conversions differed in all months (P <0.05) between taurus and zebu cattle, except in the month of May. In taurus females, conversion rates behaved similarly throughout the year, no differences were observed. We conclude that zebu cows produce more total and viable oocytes than the taurus cows, and that the production of embryos is higher in zebu cows, not only because of the increased production of oocytes, but also because of the best conversion rate. There was no seasonal variation in the production of viable and total oocytes and embryos in cows of European origin. Zebu cows produce fewer embryos during the colder periods of the year, especially in the months of April and May.